ChatGPT: a tool for scientific writing or a threat to integrity? - Silva, Thaísa Pinheiro; Ocampo, Thaís S C.; Alencar-Palha, Caio; Oliveira-Santos, Christiano; Takeshita, Wilton Mitsunari [UNESP]; Oliveira, Matheus L. (Oxford University Press (OUP), 2023)
The use of ChatGPT as a tool for writing and knowledge integration raises concerns about the potential for its use to replace critical thinking and academic writing skills. While ChatGPT can assist in generating text and suggesting appropriate language, it should not replace the human responsibility for creating innovative knowledge through experiential learning. The accuracy and quality of information provided by ChatGPT also require caution, as previous studies have reported inaccuracies in references used by chatbots. ChatGPT acknowledges certain limitations, including the potential for generating erroneous or biased content, and it is essential to exercise caution in interpreting its responses and recognize the indispensable role of human experience in the processes of information retrieval and knowledge creation. Furthermore, the challenge of distinguishing between papers written by humans or AI highlights the need for thorough review processes to prevent the spread of articles that could lead to the loss of confidence in the accuracy and integrity of scientific research. Overall, while the use of ChatGPT can be helpful, it is crucial to raise awareness of the potential issues associated with the use of ChatGPT, as well as to discuss boundaries so that AI can be used without compromising the quality of scientific articles and the integrity of evidence-based knowledge.